THE SIGNIFICANCE OF THE VAN TILLIAN METHOD IN APOLOGETICS WITH AN EXAMPLE OF ARGUMENT TO MUSLIMS - Muriwali Yanto Matalu (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2016)
Presuppositional apologetics has become a main alternative (or competitor?) for the classical apologetics which maintains evidences. Although its emergence occurred within the Reformed tradition, particularly through the effort of Cornelius Van Til and Gordon Clark, its significance goes beyond the Reformed tradition. Even the contemporary evangelical apologist, Ravi Zacharias, also utilizes presuppositional apologetics which he combines with evidentialistic method. This fact is hardly denied when we read his book "Jesus among Other Gods." Thus, the main concern of this article is regarding the significance of the presuppositional apologetics particularly in its Van Tillian form. After presenting an exposition on this method, we will see its application toward Muslims' concept of God and the idea of uniformity.